The Role of Complete Blood Count Test and General Urine Examination in Early Detection Of Risks And Diseases Affecting Women - Talib, Ruaa A. (Majallat Jāmiʻat Bābil, 2025)
A number of blood samples were collected from women in various locations across Babil Governorate. A Complete Blood Count (CBC) test was conducted to detect any general health issues these women might be experiencing. A table was prepared to investigate and assess the role or impact of blood analysis in determining their general health status. In addition to the blood test, a urine analysis was also conducted to provide a comprehensive understanding of each woman's health condition, including determining whether the woman is pregnant and identifying her age. The general appearance of the samples did not show the presence of blood or any abnormal features in terms of appearance. The results indicated that the Packed Cell Volume (PCV), which reflects the concentration of red blood cells, was generally low among all women who underwent the test. This provides an initial indication of potential anemia. Most samples showed normal red blood cell (RBC) and white blood cell (WBC) counts, although some women exhibited elevated WBC levels, likely due to the presence of infections. Platelet counts were within the normal range. In the general urine examination, the ketone levels in urine were measured and found to be within normal limits, indicating no significant issues. These levels depend on dietary patterns and hormonal changes, such as those caused by pregnancy. The number of pus cells and red blood cells in urine was also measured. The majority of samples showed elevated pus cell counts, suggesting urinary tract infections (UTIs), and elevated RBCs were also observed. However, most women did not show abnormalities related to urinary crystals or bacteria. Epithelial cells were also counted, and most samples showed elevated levels, which may indicate inflammation or infection in the urinary tract. The main issue addressed in this research is the general lack of attention to women's health until symptoms of a specific illness appear. In most cases, women only begin to prioritize their health after becoming pregnant, primarily for the well-being of the fetus. The study found that many women do not undergo regular check-ups and only begin health screenings—such as the complete blood count (CBC) test and urine analysis—after confirming pregnancy, in order to detect and prevent any potential health issues during pregnancy.